Half-life determination of 155Tb from mass-separated samples produced at CERN-MEDICIS. (December 2022) - Collins, S.M.; Robinson, A.P.; Ivanov, P.; Köster, U.; Cocolios, T.E.; Russell, B.; Webster, B.; Fenwick, A.J.; Duchemin, C.; Ramos, J.P.; Chevallay, E.; Jakobsson, U.; et al.
Abstract: Terbium-155 has been identified for its potential for single-photon emission computed tomography (SPECT) in nuclear medicine. For activity measurements, an accurate and precise half-life of this radionuclide is required. However, the currently evaluated half-life of 5.32(6) d with a relative standard uncertainty of 1.1% determines the precision possible. Limited literature for the half-life measurements of this radionuclide is available and all reported investigations are prior to 1970. Further measurements are therefore needed to confirm the accuracy and improve the precision of the half-life for its use in the clinical setting. Two samples produced and mass separated at the CERN-MEDICIS facility have been measured at the National Physical Laboratory by two independent techniques: liquid scintillation counting and high-purity germanium gamma-ray spectrometry. A half-life of 5.2346(36) d has been determined from the weighted mean of the half-lives determined by the two techniques. The half-life reported in this work has shown a relative difference of 1.6% to the currently evaluated half-life and has vastly improved the precision. Highlights: Mass separated and radiochemically purified samples used to determine the half-life. A half-life of 5.2346(36) d has been determined from two independent techniques. A relative deviation of 1.6% from current evaluated half-life observed. An order of magnitude increase in the precision has been achieved.